3D Research Challenges in Cultural Heritage II: How to Manage Data and Knowledge Related to Interpretative Digital 3D Reconstructions of Cultural Heritage - (:unkn) unknown (My University, 2016)
This book reflects a current state of the art and future perspectives of Digital Heritage focusing on not interpretative reconstruction and including as well as bridging practical and theoretical perspectives, strategies and approaches. Comprehensive key challenges are related to knowledge transfer and management as well as data handling within a interpretative digital reconstruction of Cultural Heritage including aspects of digital object creation, sustainability, accessibility,
Keywords: Cultural property; Three-dimensional imaging in archaeology